Behind the Scenes of Civil Servants: Unveiling the Factors Triggering Cyberloafing Through a Literature Review - Putri, I Gusti Agung Ayu Tribuana; Simarmata, Nicholas (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Cyberloafing refers to the behavior of using the internet for personal purposes during working hours, which can reduce productivity, including among civil servants (ASN). This study aims to examine and identify the various factors that influence cyberloafing among ASN through a literature review method. Literature searches were conducted using Google Scholar, Semantic Scholar, and Garuda, with inclusion criteria covering the years 2015–2025. Based on an analysis of 13 journal articles, the factors influencing cyberloafing were classified into two main categories: internal and external factors. Internal factors consist of individual characteristics, psychological aspects, and role-related elements inherent to employees as members of an organization. In contrast, external factors involve aspects of the work environment shaped by organizational systems and conditions. The findings indicate that cyberloafing among ASN is predominantly influenced by internal factors, although external factors also play a significant role. This review is expected to serve as an initial foundation for understanding the causes of cyberloafing among civil servants and to guide the development of more targeted policies. Furthermore, the results open opportunities for future research to explore similar factors in sectors beyond the public service.Cyberloafing merupakan perilaku menggunakan internet untuk keperluan pribadi selama jam kerja yang dapat menurunkan produktivitas, termasuk di kalangan Aparatur Sipil Negara (ASN). Penelitian ini bertujuan untuk mengkaji dan mengidentifikasi berbagai faktor yang memengaruhi cyberloafing pada ASN melalui metode kajian literatur. Pencarian literatur dilakukan melalui portal Google Scholar, Semantic Scholar, dan Garuda dengan kriteria inklusi rentang tahun 2015–2025. Berdasarkan 13 jurnal yang telah dianalisis, ditemukan bahwa faktor-faktor yang memengaruhi cyberloafing dapat digolongkan ke dalam dua kategori utama, yaitu kategori internal dan eksternal. Kategori internal terdiri dari faktor individual, psikologis, serta peran di tempat kerja yang melekat pada diri individu sebagai bagian dari organisasi. Sementara itu, kategori eksternal mencakup faktor lingkungan kerja yang berasal dari sistem dan kondisi yang dibentuk oleh organisasi. Hasil kajian menunjukkan bahwa cyberloafing pada ASN lebih dominan dipengaruhi oleh faktor internal, meskipun faktor eksternal juga memberikan kontribusi yang signifikan. Kajian ini diharapkan menjadi landasan awal dalam memahami penyebab cyberloafing pada ASN serta memberikan arah bagi perumusan kebijakan yang lebih tepat sasaran. Selain itu, hasil ini juga membuka peluang bagi penelitian selanjutnya untuk menelaah faktor-faktor serupa dalam konteks sektor lain di luar ASN.